Strategi Bersaing Bisnis Di Bidang Digitalisasi Pengarsipan Dokumen (Studi Kasus Pada PT. Expert Indonesia) - Luthfiyyah Nahdah Zahra; Mercy Spesa Devina De Fretes (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract. Advances in information and communication technology have encouraged the digitalization of documents which offers accuracy, fast access, time efficiency and security of company data. PT Expert Indonesia, which started document digitization services in 2010, helps companies manage documents with cutting-edge technology and an experienced team. However, competition with companies such as PT Permata Graha Nusantara demands that PT Expert Indonesia to implement the right business strategy to remain competitive. This research uses a descriptive qualitative approach. The data analysis technique used is SWOT analysis, by identifying the company's strengths, weaknesses, and opportunities and threats so that it can produce alternative strategies to increase competitiveness. The research results show that PT Expert Indonesia has implemented a competitive strategy well, although there are still aspects that need to be improved. Obstacles faced include difficulties in obtaining ANRI certification, large volumes of work, damaged documents, and the unpopularity of digitalization services among companies. Various efforts have been made to overcome these obstacles, such as quick follow-up of problems, compliance with procedures and regulations, and market education about the importance of document digitization. PT Expert Indonesia can carry out more in-depth competitor analysis, intensive market education, and expand services through collaboration with governments other than BUMN and private companies in various sectors. Keywords: BusinessCompetitive Strategy, Document digitalization